Anti-inflammatory and antioxidant activities of ethylacetate fraction of Sida linifolia L. (Malvaceae) - Nicodemus Emeka Nwankwo; Emmanuel Chigozie Aham; Emmanuel Henry Ezenabor; Diana-Mary Ginika Chidozie (International Journal of Plant Based Pharmaceuticals, 2023)
Sida linifolia L., a known weed found in West Africa and other parts of the world, is being used in African traditional medicine for many purposes, including the relief of uncomfortable teething, and the prevention of malaria. This study aimed to fractionate the crude extract of S. linifolia and determine the anti-inflammatory, and antioxidant properties of the most potent fraction. In the examination of anti-inflammatory compounds, in vitro tests for platelet aggregation, albumin denaturation, protease, and phospholipase A2 were utilized. To assess the in vivo anti-inflammatory effects, rat paw edema was induced with carrageenan and egg albumin. The total antioxidant capacity (TAC), 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing power (FRAP), and nitric oxide (NO) assays were used in the in vitro antioxidant assessment. The result of the phytochemical screening revealed that there were varying concentrations of terpenoids, saponins, steroids, alkaloids, flavonoids, tannins, and other phenols. The ethylacetate leaf fraction of S. linifolia EALFSL displayed robust, concentration-dependent anti-inflammatory effects by significantly inhibiting hypotonicity-and heat-induced hemolysis, platelet aggregation, protein denaturation, protease activity, and phospholipase A2 activity, which were comparable to those of the reference drugs (aspirin/prednisolone). In vivo studies also revealed that EALFSL was able, at different doses, to inhibit the progress of carrageenan-induced rat paw edema and egg albumin models. Though it was less active than the butylated hydroxytoluene BHT (0.30 mg/ml), ascorbic acid (0.32-0.50 mg/ml), and gallic acid (0.47 mg/ml), the EALFSL fraction's IC50 values ranged from 0.93 to 1.20 mg/ml. The results demonstrated that EALFSL has significant concentration-dependent antioxidant activity. These suggest that the ethylacetate leaf fraction of S. linifolia possesses anti-inflammatory and antioxidant effects.